Strategi Dinas Sosial Dalam Penertiban Anak Jalanan Di Kota Makassar - Ali, Mustafa; Muhammadiah, Muhammadiah; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to determine the Social Service Strategy in the Control of Street Children in Makassar City. The number of informants in this study was 9 people. This study used qualitative with a type of phenomenological research that emphasized the subjectivity of human life experiences. Data collection techniques used the method of observation, interviews and documentation. Data analysis used interactive analysis models. The results showed that the Social Service Strategy in the Control of Street Children in Makassar City had not been fully implemented optimally. This was seen from the aspect of the organizational structure, especially the social service, it has worked well to always pay special attention to Street Children, the program strategy also provided guidance in stages to Street children who had been raided, the strategy of supporting resources that control Makassar Street Children was supported not only from social services but the involvement of local communities, and institutional strategies that the government's strategy in dealing with Makassar City Street Children collaborated with the police in dealing with street children which could be unsettling for road users. Keywords: Strategy, Ordering Street Children